Pengaruh Work - Life Balance Dan Lingkungan Kerj Terhadap Kepuasan Kerja Pegawai Aparatur Sipil Negara (ASN) di Kantor Unit Penyelenggara Bandar Udara (UPBU) Kelas III Andijemma Masamba - Putriama Supardi, Musdalifah; Kasran, Muhammad; Sampetan, Suparni (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of work-life balance on job satisfaction with the mediating role of the work environment among Civil Servants (ASN) at the Class III Andi Jemma Masamba Airport Authority Office. Using a quantitative causal approach, data were collected from 30 ASN through a Likert-scale questionnaire and analyzed using PLS-SEM with SmartPLS 3. The results indicate that work-life balance positively affects the work environment and job satisfaction, while the work environment significantly enhances job satisfaction and mediates the relationship between work-life balance and job satisfaction. These findings imply that organizations should strengthen work-life balance policies and create supportive work environments to improve employee satisfaction. Keywords: Work-life balance; work environment; job satisfaction; civil servants; mediation effect; PLS-SEM